Halal Medicine Selection Process in Sharia-Certified Hospital - Ningtyas, Palupi Fatma; Permana, Iman; Rosa, Elsye Maria; Jaswir, Irwandi (Indonesian Journal of Halal Research, 2022)
A drug formulary free of haram substances is one of the standards in medicine service. The purpose of this study is to analyze the implementation of the halal medicine selection process in Nur Hidayah Hospital Yogyakarta. It is qualitative research using a case study method. Data were collected using interviews, observation, and documentation techniques. The study reveals four themes in the selection process for halal medicine implementation at Nur Hidayah Hospital. The themes are sharia-based medicine screening, halal label limitations, haram medicine use based on doctor-patient agreement using sharia informed consent, and halal statements from drug manufacturers. The research concluded that sharia principles had been implemented in the medicine selection process at Nur Hidayah Hospital, but the number of halal-labeled medications remains limited. The use of non-halal substances in medicine through a doctor-patient agreement based on sharia informed consent. Halal statements from pharmaceutical companies support implementing the halal lifestyle in hospitals.